Attendance of MSM at Genitourinary Medicine services in England: implications for selective HPV vaccination programme (a short communication). (9th March 2017) - Bayley, Jake; Mesher, David; Nadarzynski, Tom; Hughes, Gwenda; Soldan, Kate
Abstract : Background: Human papillomaviruses (HPV) immunisation programmes for female adolescents in the UK offer relatively little benefit to men who have sex with men (MSM). Targeted HPV vaccination for MSM may reduce the high incidence of HPV-related disease among MSM. We used national data from sexual health clinics to calculate the number of MSM attending these clinics throughout England from 2009 to 2014 and to identify their characteristics, to inform the implementation of a targeted HPV vaccination programme in MSM. Methods: We used the Genitourinary Medicine Clinic Activity Dataset (GUMCADv2) to obtain data for men aged 15–70 years who had attended a GUM clinic in England from 2009 to 2014. We analysed both numbers of MSM attending and number of GUM attendances, age at first attendance, ethnicity and geographical area of the clinic in England. Results: A total of 374 983 MSM attended sexual health services in England between 2009 and 2014. Median age of presentation was 32 years (IQR 25–41) and showed regional geographical variation. Of all men attending sexual health clinics in England, the highest proportion of those identifying as MSM was in London (21%). Excluding visits within 1 month of an initial attendance, 49% of all MSM re-attended within 12 months and 58% within 24 months. MSM aged ≥36 years reattended more frequently than younger MSM. 51% reattended at least twice within 24 months of initial visit. Conclusions: The majority of MSM reattend clinic at least once within a 24-month period, potentially facilitating the delivery of a three-dose HPV vaccination programme. This would reduce the burden on sexual health clinics and cost to local authorities due to extra visits if HPV vaccination were to be delivered through these services.